EVALUATION MAPPING TO ASSESS URBAN PARK SUITABILITY ELEMENTS - Hastuti, Sulestyaning; Jordan, Nadia Almira; Putra, Rulliannor Syah; Artanti, Tiara Harya (Journal of Architecture&ENVIRONMENT, 2024)
Urbanization, characterized by dense populations and demanding lifestyles, necessitates a commensurate emphasis on urban planning that prioritizes livability. Green spaces, particularly urban parks, are fundamental to this endeavor, serving as vital counterpoints to the built environment and fostering social interaction while promoting well-being. This study investigates Ulin Urban Park in Kutai Kartanegara Regency, East Kalimantan, a region grappling with mental health challenges, including instances of suicide linked to depression, some occurring within the park itself. Recognizing the crucial role of accessible and well-designed green spaces in mitigating such issues, this research employs an evaluative mapping approach to analyze the park's landscape elements. By assessing the availability and quality of these elements against established standards and suitability indicators, the study aims to identify areas for improvement in Ulin Urban Park's design and infrastructure. Field observation through photo taking was done to collect the existing condition of the park’s landscape elements in supporting users’ activities. The findings highlight specific areas where the park's soft and hard character elements, furniture, circulation, utilities, microclimate, and management of noise and odor require improvement and attention. The diversity of vegetation that enhances biodiversity could improve the attractiveness, while the quality of seating areas and other structures will improve comfort and aesthetic appeal. Such improvement in the pathways for both segments will also support the flow and accessibility.